The effect of foreign ownership on dividend policy : evidence from China - Yan, XiaoFang (2018)
This study examined the relationship between foreign ownership and dividend policy in the Chinese market. Panel logistic regression was employed to explain the effect of foreign ownership on the choice "to pay" or "not to pay" dividends. Panel model used in this study is constructed by 142 companies’ data with 1988 observations involving foreign ownership listed on the Shenzhen Stock Exchange from 2003 to 2016. Findings indicate that a higher level of foreign ownership is associated with a significantly higher probability of paying dividend. This finding is consistent to agency theory and clientele effect theory. The significant positive result for retained earnings to total equity provides support to the implication stated in the life cycle theory. However, the signaling theory is not supported as the results show an insignificant relationship between cash flow and dividend payment, and between investment opportunities and dividend payment. The findings of this study indicates that foreign shareholders in the Chinese market have high preference for dividend paying companies, especially for large companies with low leverage. Hence for investors who prefer dividends, they should invest in companies with foreign ownership as the likelihood of these companies to pay dividend is higher.